2018
DOI: 10.3390/educsci8030150
|View full text |Cite
|
Sign up to set email alerts
|

A Community Based Participatory Approach to Training Young Adults to Design and Implement a Social Marketing Framed Lifestyle Intervention on Their College Campus

Abstract: Background: Using a Community-Based Participatory Research (CBPR) approach may increase the likelihood of relevance and acceptability of the designed intervention, especially on a college campus. Furthermore, recruiting and training college students to design a social marketing framed healthy lifestyle intervention for their peers will allow the intervention to be tailored to the needs of the campus. Objectives: To describe the process of online-course training college students to develop a campus-based, socia… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 36 publications
0
7
0
Order By: Relevance
“…According to Erikson’s stages of development [ 3 ], young people at this stage are faced with shifting identities, and the different identities might have a persistent and far-reaching impact on their behaviors [ 1 , 78 ]. However, most extant studies on emerging adult-specific lifestyle interventions merely consider the campus environment when carrying out community-based practices [ 70 , 74 ]. Workers in emerging adulthood have always been neglected.…”
Section: Discussionmentioning
confidence: 99%
“…According to Erikson’s stages of development [ 3 ], young people at this stage are faced with shifting identities, and the different identities might have a persistent and far-reaching impact on their behaviors [ 1 , 78 ]. However, most extant studies on emerging adult-specific lifestyle interventions merely consider the campus environment when carrying out community-based practices [ 70 , 74 ]. Workers in emerging adulthood have always been neglected.…”
Section: Discussionmentioning
confidence: 99%
“…During the 15-week course, SMEI students were trained to develop a peer-led social marketing campaign intervention focused on three main topic areas: diet, physical activity, and stress management [ 27 ]. Within Get Fruved, these areas were targeted as specific zones of healthy living that can impact well-being long term.…”
Section: Project Overviewmentioning
confidence: 99%
“…The purpose of this article is to describe changes in self-reported behaviors of SMEI and PM after training, designing, and implementing the Get Fruved pilot intervention [ 27 ] compared to control students. To the best of our knowledge, this is the first study assessing the behavior change of young adult community partners across the course of designing and implementing a health promotion intervention for their peers.…”
Section: Purposementioning
confidence: 99%
“…Community-based participatory research approaches have been shown to lead to sustainable health behavior change [ 15 ]. Among college student populations, the reduction of risky health behaviors has been a foci of many CBPR interventions, such as reducing excessive alcohol consumption, improving nutrition and dietary quality, reducing sedentary lifestyle, suicide prevention, reduction and awareness of substance abuse, among others [ 16 , 17 , 18 ]. Using a community-wide approach to health programming has also proven to have a positive long-term return on investment by reducing work absenteeism and healthcare costs associated with obesity and chronic disease [ 19 ].…”
Section: Introductionmentioning
confidence: 99%
“…A study by Barr et al utilized a similar approach to lead a college course for students who were interested in aiding with the development of a social marketing and environmental intervention [ 24 ]. Authors found that participating in the courses resulted in greater physical activity and less stress compared to a control group of students, and the social marketing campaign that was developed was tailored to their peers’ health needs [ 17 ].…”
Section: Introductionmentioning
confidence: 99%